2018
DOI: 10.7602/jmis.2018.21.4.154
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Laparoscopic Surgery for Intussusception in Pediatric Patients and Risk of Bowel Resection

Abstract: Intussusception is a common cause of intestinal obstruction in children. While most patients can be treated by enema reduction, about 20% require surgery. We investigated the usefulness and feasibility of laparoscopic surgery and the intraoperative risk of bowel resection. Methods: We retrospectively reviewed pediatric patients who underwent surgery for intussusception from 2010 to 2017. We collected data for age, gender, body weight, associated symptoms, duration of symptoms, white blood cell count, operating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
2
3
0
1
Order By: Relevance
“…Laparoscopy has been reported to be effective and without major complications for the management of intussusception[ 1 , 2 ], supporting the present study. In the present study, the success rate of laparoscopy was 88%, which is within the 79%-90% range reported by many case series[ 1 - 3 ]. Nevertheless, the use of laparoscopy remains controversial because laparoscopic intussusception reduction has a high rate of conversion to laparotomy, as high as 70% in some reports[ 4 ].…”
Section: Methodssupporting
confidence: 88%
See 1 more Smart Citation
“…Laparoscopy has been reported to be effective and without major complications for the management of intussusception[ 1 , 2 ], supporting the present study. In the present study, the success rate of laparoscopy was 88%, which is within the 79%-90% range reported by many case series[ 1 - 3 ]. Nevertheless, the use of laparoscopy remains controversial because laparoscopic intussusception reduction has a high rate of conversion to laparotomy, as high as 70% in some reports[ 4 ].…”
Section: Methodssupporting
confidence: 88%
“…It was found that the terminal ileum had duplication malformations that were managed with intestinal resection and anastomosis. With the improvement of laparoscopic techniques and instrumentation, we believe that laparoscopic surgery will not be contraindicated by age or intestinal resection because minimally invasive surgery through a small umbilical incision can be achieved even for intestinal resection[ 1 - 3 ].…”
Section: Methodsmentioning
confidence: 99%
“…12 Song et al were unsuccessful in reducing any patient on the operation table by air reduction during laparoscopy. 13 In one patient, after laparoscopy, we noticed perforated appendicitis. This matter may be due to preoperative hydrostatic reduction complications or failure in the diagnostic process.…”
Section: Discussionmentioning
confidence: 95%
“…In this survey, we did hydrostatic reduction three times (if required) for all patients before surgery to select surgical intussusceptions. [10][11][12][13] We performed another hydrostatic reduction on the operation table under the guidance of laparoscopic exploration. In intra-operative reduction, all attempts were unsuccessful.…”
Section: Discussionmentioning
confidence: 99%
“…O tubo, então, é inserido no jejuno com cuidado de forma em que se garanta espaço suficiente, evitando o refluxo alimentar através do mesmo. A sutura purse string então fixa o tubo garantindo o seu adequado posicionamento (SONG, 2023;SIOW et al, 2017).…”
Section: Técnicas De Jejunostomiaunclassified